Sistem Informasi Penjualan Roti Dan Kue Heni Bakery Pada Home Industry Desa Bis 2 Pekan Tolan Berbasis Web - Lestari, Sri Indah (Journal of Computer Science and Information System(JCoInS), 2021)
Bread and Cake Heni Bakery is a store that is engaged in the sale of cakes and bread located at Jalan Simpang Kayu Manis, Bus Village 2 Tolan Weekend, Labuhanbatu Selatan, North Sumatra. Until now the Bread and Cake Heni Bakery is still finding many problems and obstacles in sales, namely the process of promotion to the general public, especially around Labuhanbatu. Based on the above problems the author designed and made an information system on Heni Bakery Bread and Cake. This information system applies the waterfall model in its development, and is built with the PHP programming language and uses MySql. The design of the program will be done, with a reference program that is made using the UML (unifed Modeling Language) method. Information systems for selling bread and cakes are very important in establishing a business because it can be a benchmark in the development and achievement of targets in entrepreneurship. With the existence of a bread sales website and heni bakery cake, it is expected to reach the manager's expectations in promoting their products to the wider community.